Optimal Use of Wire-Assisted Techniques and Precut Sphincterotomy - Tae Hoon Lee; Sang-Heum Park (Korean Society of Gastrointestinal Endoscopy, 2016)
Various endoscopic techniques have been developed to overcome the difficulties in biliary or pancreatic access during endoscopic retrograde cholangiopancreatography, according to the preference of the endoscopist or the aim of the procedures. In terms of endoscopic methods, guidewire-assisted cannulation is a commonly used and well-known initial cannulation technique, or an alternative in cases of difficult cannulation. In addition, precut sphincterotomy encompasses a range of available rescue techniques, including conventional precut, precut fistulotomy, transpancreatic septotomy, and precut after insertion of pancreatic stent or pancreatic duct guidewire-guided septal precut. We present a literature review of guidewire-assisted cannulation as a primary endoscopic method and the precut technique for the facilitation of selective biliary access.